External beam radiotherapy versus vaginal brachytherapy in patients with stage II endometrial cancer: a systematic review and meta‐analysis. Issue 6 (June 2020) - Narasimhulu, Deepa Maheswari; Cope, Adela; Riaz, Irbaz Bin; Petersen, Ivy; Cilby, William; Langstraat, Carrie; Glaser, Gretchen; Kumar, Amanika; Cappuccio, Serena; Murad, Hassan; West, Colin; Mariani, Andrea
ABSTRACT : Objective : The choice of adjuvant treatment for women with stage II endometrial cancer is challenging, given the known increase in morbidity with external beam radiation compared with vaginal brachytherapy, and the lack of consensus on its benefits. We summarized the evidence on survival and recurrence for stage II endometrial cancer, defined as cervical stromal invasion, after adjuvant postoperative external beam radiotherapy and vaginal brachytherapy. Methods : We searched the MEDLINE, EMBASE, CENTRAL, and Scopus databases from inception to January 2019 to identify studies that compared adjuvant postoperative external beam radiotherapy with or without vaginal brachytherapy and vaginal brachytherapy alone in stage II endometrial cancer. Our primary outcome was the locoregional recurrence rate, defined as recurrence in the pelvis or vagina. Secondary outcomes included the rate of recurrence at any site, distant recurrence rate, vaginal recurrence rate, pelvic recurrence rate, and 5 year overall survival. Study selection, assessment, and data abstraction were performed by an independent set of reviewers. Random effects models were used to synthesize quantitative data. Results : We included 15 cohort studies reporting data on 1070 women. Most women with stage II endometrial cancer (848/1070, 79.3%) were treated with external beam radiotherapy with or without vaginal brachytherapy. Subgroup analysis was stratified by whether >90% of the women included underwent pelvic lymph node assessment (sampling or full dissection). Locoregional recurrence (pelvic and vaginal recurrence) was significantly reduced with external beam radiotherapy with or without vaginal brachytherapy compared with vaginal brachytherapy alone (14 studies (n=1057); odds ratio (OR) 0.33 (95% confidence interval (CI) 0.16 to 0.68); I 2 =5%) regardless of pelvic lymph node assessment. Most women (81.8%) who recurred locoregionally had a least one uterine risk factor (grade 3 tumor, myometrial invasion >50%, or lymphovascular invasion). There was no difference in overall survival with external beam radiotherapy with or without vaginal brachytherapy compared with vaginal brachytherapy alone (five studies (n=463); OR 0.78 (95% CI 0.34 to 1.80); I 2 =48%). Conclusions : External beam radiotherapy with or without vaginal brachytherapy decreased the locoregional recurrence threefold for stage II endometrial cancer, regardless of pelvic lymph node assessment. Most women who suffered recurrence locoregionally had a least one high risk factor. Vaginal brachytherapy alone may be sufficient therapy for node negative stage II endometrial cancer without uterine risk factors, while those with uterine risk factors should be considered for external beam radiotherapy with or without vaginal brachytherapy to improve locoregional control.